Incidence and Outcomes of Contrast-Induced AKI Following Computed Tomography - Weisbord, Steven D. (American Society of Nephrology, 2008)
Background and objectives: Most studies of contrast-induced acute kidney injury (CIAKI) have focused on patients undergoing angiographic procedures. The incidence and outcomes of CIAKI in patients undergoing nonemergent, contrast-enhanced computed tomography in the inpatient and outpatient setting were assessed. Design, setting, participants, & measurements: Patients with estimated glomerular filtration rates (GFRs) <60 ml/min per 1.73 m(2) undergoing nonemergent computed tomography with intravenous iodinated radiocontrast at an academic VA Medical Center were prospectively identified. Serum creatinine was assessed 48 to 96 h postprocedure to quantify the incidence of CIAKI, and the need for postprocedure dialysis, hospital admission, and 30-d mortality was tracked to examine the associations of CIAKI with these medical outcomes. Results: A total of 421 patients with a median estimated GFR of 53 ml/min per 1.73 m(2) were enrolled. Overall, 6.5% of patients developed an increase in serum creatinine ≥25%, and 3.5% demonstrated a rise in serum creatinine ≥0.5 mg/dl. Although only 6% of outpatients received preprocedure and postprocedure intravenous fluid, <1% of outpatients with estimated GFRs >45 ml/min per 1.73 m(2) manifested an increase in serum creatinine ≥0.5 mg/dl. None of the study participants required postprocedure dialysis. Forty-six patients (10.9%) were hospitalized and 10 (2.4%) died by 30-d follow-up; however, CIAKI was not associated with these outcomes. Conclusions: Clinically significant CIAKI following nonemergent computed tomography is uncommon among outpatients with mild baseline kidney disease. These findings have important implications for providers ordering and performing computed tomography and for future clinical trials of CIAKI.